Geguritan Ni Sumala: Suatu Kajian Filologis - Krismayanti, Luh Gede; Suteja, I Wayan; Nala Antara, I Gde (Humanis; Vol 25 No 3 (2021), 2021)
This research is entitled “ Geguritan Ni Sumala : Philological Studies”. Assessment of Geguritan Ni Sumala uses philological theory. This study aims to obtain the text of Geguritan Ni Sumala which approaaches the original. The data supply phase uses the observation method and simak method helped by note taking technique. Next, in data analysis phase using comparative descriptive method, transliteration uses standard transliteration method, following by a comparation of three texts through text criticism, text edition using the legger method, the translation uses combination literal translation and idiomatic translation. In the stage of presenting the result of data analysis using formal and informal method by deductive-inductive tecnique also assisted by exposure, tables, and themes. The text edition is complemented by criticism apparatus which is presented separately and translation is also presented separately with the source text. The result of this study are, from the three of GNS manuscripts that have been compared through text criticism there are some copy/write errors from each text such as substitution, adition, omission, lakuna, interpolation, ditography, transposition, and corrupt. By correcting the copy error presented Geguritan Ni Sumala text which assumed to be correct based on the evidence three of contained manuscripts. Geguritan Ni Sumala uses Balinese Kawi language. Next in text edition for literacy guidelines used are Acri and Griffiths opinions (2014: 371-372) and combined with Damais opinions (1995: 125). aside from that, the spelling used in text edition are spelling guidelines for Balinese script pairs with Latin letters and Balinese letters also guidelines Pasang Aksara Bali . Indonesian translations are also included in the Geguritan Ni Sumala text.